1993
DOI: 10.5144/0256-4947.1993.172
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing Patterns of Ambulatory Care Physicians in Saudi Arabia

Abstract: The drug prescribing patterns of ambulatory care physicians in the Ministry of Health (MOH) hospitals were studied by examining 10,291 systematically sampled prescriptions obtained from 22 general hospitals covering the various health regions within Saudi Arabia. An audit of prescription information revealed that documentation was not generally complete. Information relating to patient age and diagnosis was missing in 18.6% and 9.8% of the prescriptions, respectively. The average number of drugs per prescripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
60
4

Year Published

1999
1999
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(75 citation statements)
references
References 21 publications
11
60
4
Order By: Relevance
“…Also, 109(49.3%) of pharmacists participating in this study believed that anti-diabetics, anti-hypertensives are not POMs. This is similar to a study carried out in Saudi Arabia, where 85.4% of pharmacists are confused between POM and OTC medications [20]. In spite of the fact that antibiotics are under POM category, this study found that the observer, who played the role of a patient, received antibiotics after a verbal request without a prescription form, 206 (96.3%), pharmacies out of the 218 pharmacies participating in this study.…”
Section: Iv-resultssupporting
confidence: 68%
“…Also, 109(49.3%) of pharmacists participating in this study believed that anti-diabetics, anti-hypertensives are not POMs. This is similar to a study carried out in Saudi Arabia, where 85.4% of pharmacists are confused between POM and OTC medications [20]. In spite of the fact that antibiotics are under POM category, this study found that the observer, who played the role of a patient, received antibiotics after a verbal request without a prescription form, 206 (96.3%), pharmacies out of the 218 pharmacies participating in this study.…”
Section: Iv-resultssupporting
confidence: 68%
“…This is in line with other studies in Saudi Arabia. 8,9 It is well known that women suffer more ill health, 12,13 use the health services more, and consult more frequently than men. 13,14 Possible explanations for a lower female prescription rate include the following: 1) a proportion of female visits are for preventive reasons (e.g., antenatal visits) that may not require prescriptions; and 2) men may exert greater pressure on their physicians to issue prescriptions.…”
Section: Discussionmentioning
confidence: 99%
“…One of these studies was hospital-based, 8 and another used a limited sample in mostly rural areas. 9 The present study is the most extensive in a large urban area, aiming to assess the prescribing pattern of the primary health care (PHC) physicians in the studied PHC centers in the city of Riyadh, the capital of Saudi Arabia.…”
mentioning
confidence: 99%
“…In fact, many articles found non-compliance towards primary health care appointments, antenatal visits, and antiepileptic therapy [10,11]. Several studies have shown that one of the major problems in health care is non-compliance with the prescribed medications.…”
Section: Discussionmentioning
confidence: 99%